PENGARUH PEMBERDAYAAN STRUKTURAL DAN KEBIJAKAN TUNJANGAN KINERJA TERHADAP AKUNTABILITAS KINERJA PEGAWAI PADA KANTOR BPKD PEMERINTAH KABUPATEN WONOGIRI - Estiningtyastuti Estiningtyastuti (JURNAL ILMIAH EDUNOMIKA, 2022)
This research aims to empirically test the influence of structural empowerment and compensation policies on employee performance accountability at the Office of the Regional Financial Management Agency (BPKD) of Wonogiri regency. The study involved 110 respondents through questionnaires that had been distributed. Based on data quality tests, research data is declared to meet validity and reliability. The study used multiple linear regression analyses that had previously been tested on classical assumptions. Based on the results of the study showed that structural differentiation has a positive effect on performance accountability and performance allowance policies have a positive effect on performance accountability. The higher the intensity of local governments in conducting structural empowerment, the higher the level of performance accountability provided by civil servants. In addition, with the performance allowance, the aspect of transparency and accountability of performance provided by civil servants will be higher. Researchers suggest to be consistent in carrying out structural empowerment so that institutions can run optimally.